Un análisis histórico sobre la educación escolar indígena en el estado de Rondonia - Jonatha Daniel Santos; Rozane Alonso Alves (Universidade Federal de Rondônia, 2020)
The text on screen aims to show the historical aspects of public policies and practices of indigenous school education in the state of Rondônia. For this, we use the resources of bibliographic research using public sources for data collection. It is an analysis of official documents and academic productions that focused on indigenous issues in the state of Rondônia. The results show that public policies started to compose the indigenous itinerary in the Amazonian space, mainly after the Federal Constitution of 1988. They also show that the discourses about the Amazonian indigenous populations come from Westernized thoughts, which placed / put the indigenous peoples in a position of subalternities, on the other hand, the indigenistas and indigenas that militarize / militate for and on the indigenous education since the colonization made possible, in the midst of the movements of struggles, to create spaces of resistance in favor of the specific and differentiated indigenous school education for these peoples . It was from these spaces of resistance that the indigenous populations began to lead the spaces for training and school activities. Their stories were and are marked by tensions and challenges in search of guaranteeing and maintaining their rights, legally recommended in the country.